Study of the Efficacy of Cognitive Restructuring Teaching at Student\'s Attribution Style and Academic Performance - Niloofar Mikaeili; Hossein Zare; Aref Akbari Alhashem (Iranian Rehabilitation Journal, 2010)
Objectives: One of the education ministry’s concerns in high schools is the problem of academic achievement. The researches have mentioned that student’s false attribution and absence of scholastic counseling service are the most important factors affecting student’s low performance and achievements. The main goal of this research was to study the rate of cognitive reconstructive effect on attribution style and girl students’ academic performance at high school in Khalkhal.